Pembuatan Sistem Surat Bebas Komdisma Bebasis Website di Komisi Disiplin dan Kemahasiswaan SV IPB - Diana Putri Rahmani; Merry Ardelia Wirastuti; Nabila Fakhiratunisa; Kaisar Renaisance Al-ars; Mochamad Farras Fauzan; Joddy Lintar Balle; Muhammad Shubhi Maulana; Mira Fitria Dewi; Tria Febriayanti; Vandame Ronald Suhada; Naufal Alif Falah; Gema Parasti Mindara; Ridwan Siskandar (Jurnal Sains Indonesia, 2021)
The Discipline and Student Affairs Commission of SV IPB (KOMDISMA-SVIPB) is a unit that handles disciplinary and student affairs issues of SV IPB students. KOMDISMA-SVIPB provides services related to discipline and student affairs for students such as good behavior letters, komdisma free letters, and matters related to student organizations and student associations at SV IPB. KOMDISMA-SVIPB has a duty to provide komdisma free letters to final year students. In order to facilitate the task of KOMDISMA-SVIPB in giving free letters to final year students, a website based system is needed that is easy to use by the user in a predetermined process. The method used in making this komdisma free letter system is the Scrum methodology. The stages contained in the Scrum methodology are Pregame, Game, and Postgame. The result of this system is a komdisma free letter that has been signed by the chairman of KOMDISMA-SVIPB and can be downloaded by students from the system that has been created.